River fragmentation and barrier impacts on fishes have been greatly underestimated in the upper Mekong River. (1st February 2023) - Sun, Jingrui; Du, Weilong; Lucas, Martyn C.; Ding, Chengzhi; Chen, Jinnan; Tao, Juan; He, Daming
Abstract: River barriers reduce river connectivity and lead to fragmentation of fish habitats, which can result in decline or even extinction of aquatic biota, including fish populations. In the Mekong basin, previous studies have mainly focused on the impacts of large dams but ignored the impacts of small-scale barriers, or drew conclusions from incomplete barrier databases, potentially leading to research biases. To test the completeness of existing databases and to evaluate the catchment-scale fragmentation level, a detailed investigation of river barriers for the whole Upper Mekong (Lancang catchment) was performed, by conducting visual interpretation of high-resolution remotely sensed images. Then, a complete catchment-scale barrier database was created for the first time. By comparing our barrier database with existing databases, this study indicates that 93.7% of river barriers were absent from the existing database, including 75% of dams and 99.5% of small barriers. Barrier density and dendritic connectivity index (DCID and DCIP ) were used to measure channel fragmentation within the catchment. Overall, 50.5% of sub-catchments contained river barriers. The Middle region is the most fragmented area within the Lancang catchment, with a median [quartiles] barrier density of 5.34 [0.70–9.67] per 100 km, DCIP value of 49.50 [21.50–90.00] and DCID value of 38.50 [9.00–92.25]. Furthermore, since 2010, distribution ranges of two representative fish species Schizothorax lissolabiatus (a rheophilic cyprinid) and Bagarius yarrelli (a large catfish) have reduced by 19.2% and 32.8% respectively, probably due in part to the construction of river barriers. Our findings indicate that small-scale barriers, in particular weirs and also small dams are the main reason for habitat fragmentation in the Lancang and must be considered alongside large dams in water management and biodiversity conservation within the Mekong. Graphical abstract: Image 1 Highlights: 50.5% of sub-catchments in the Upper Mekong are impacted by river barriers. Small barriers are the main causes of river fragmentation in the Upper Mekong. The Middle region of the Upper Mekong is the most fragmented region. Barrier construction has reduced habitat for both migratory and locally-resident fish species.